Effects of Pyrenean contraction on salt structures of the offshore Parentis Basin (Bay of Biscay) - Ferrer, O.; Roca, E.; Jackson, M. P. A.; Muñoz, J. A. (TRABAJOS DE GEOLOGÍA, 2009)
Structural analysis of old industrial 2D seismic surveys recently reprocessed from the offshore Parentis Basin reveal that salt tectonics played an important role in the basin evolution. Salt structures are mainly located in the edges of the basin, where Jurassic-Lower Cretaceous infill sequences are thinner and allowed salt anticlines and diapirs to form. Salt structures are more evolved in the east. Folds cored by Triassic evaporites and stocks created during Mesozoic times, absorbed almost all the shortening during the Pyrenean orogeny forming squeezed diapirs, salt glaciers, and welds, some of which were later reactivated as reverse faults. No new diapirs formed during the Pyrenean compression and salt tectonics ended with the termination of the Pyrenean orogeny in the middle Miocene.